2014
DOI: 10.1002/2014gl060544
|View full text |Cite
|
Sign up to set email alerts
|

Sea level anomalies exacerbate beach erosion

Abstract: Sea level anomalies are intra-seasonal increases in water level forced by meteorological and oceanographic processes unrelated to storms. The effects of sea level anomalies on beach morphology are unknown but important to constrain because these events have been recognized over large stretches of continental margins. Here, we present beach erosion measurements along Onslow Beach, a barrier island on the U.S. East Coast, in response to a year with frequent sea level anomalies and no major storms. The anomalies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Unlike storm surge, this event caused persistent and widespread coastal flooding 22 even without apparent weather processes. In terms of beach erosion, the impact of the 2009-2010 SLR event is almost as significant as some hurricane events 42 . For the twenty-first century, modelling results suggest that the increase in the greenhouse gas concentrations is likely to cause more extreme SLR events on the interannual time scale along this densely populated coast.…”
Section: Discussionmentioning
confidence: 98%
“…Unlike storm surge, this event caused persistent and widespread coastal flooding 22 even without apparent weather processes. In terms of beach erosion, the impact of the 2009-2010 SLR event is almost as significant as some hurricane events 42 . For the twenty-first century, modelling results suggest that the increase in the greenhouse gas concentrations is likely to cause more extreme SLR events on the interannual time scale along this densely populated coast.…”
Section: Discussionmentioning
confidence: 98%
“…Much attention has been given in recent years to potential connections between SLR and long-term climatic changes in AMOC and the GS (Levermann et al 2005;Boon 2012;Ezer and Corlett 2012;Sallenger et al 2012;Ezer 2013Ezer , 2015Ezer et al 2013;Kopp 2013;Yin and Goddard 2013;Srokosz and Bryden 2015). Less attention was given to shortterm variations in the GS which may cause periods of days, weeks, or months with anomalously high water that increase the risk of tidal flooding (Sweet et al 2009;Ezer and Atkinson 2014;Goddard et al 2015) and beach erosion (Theuerkauf et al 2014). Currently, water level prediction models are driven mostly by tides and local winds, so they may not be able to accurately simulate those remote, unpredictable and sometimes coherent anomalies as seen in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Monthly MSL data from 2009 to 2015 indicate that sea level in the study area was −0.028 ± 0.062 m NAVD88 (mean ± SD ) (Figure b). Prior to the start of scanning, the study area experienced prolonged levels of high water from frequent sea‐level anomalies during the fall and winter of 2009–2010 that persisted for 5 months (Theuerkauf et al., ). The sea‐level peak in 2009 corresponds to the November Mid‐Atlantic nor'easter that spawned from the remnants of Hurricane Ida (deemed Nor'Ida).…”
Section: Resultsmentioning
confidence: 99%
“…Losada et al (2013) demonstrated that interannual shifts in sea level in other areas of the Atlantic Ocean can be on the order of 4-12 cm, with ENSOinduced sea-level shifts exceeding historical RSLR and an increased frequency in sea-level extremes occurring in recent decades. Shortterm elevations in sea level are responsible for more frequent flooding along the U.S. East Coast (Ezer & Atkinson, 2014) and increased coastal erosion (Theuerkauf, Rodriguez, Fegley, & Luettich, 2014). These fluctuations in sea level may have a marked impact on coastal and estuarine habitats as their regularity and longevity are expected to increase (Ezer & Atkinson, 2014).…”
Section: Introductionmentioning
confidence: 99%